Cross-Cultural Examination of Links between Parent–Adolescent Communication and Adolescent Psychological Problems in 12 Cultural Groups - Sabina Kapetanovic (2020)
© 2020, The Author(s). Internalizing and externalizing problems increase during adolescence. However, these problems may be mitigated by adequate parenting, including effective parent–adolescent communication. The ways in which parent-driven (i.e., parent behavior control and solicitation) and adolescent-driven (i.e., disclosure and secrecy) communication efforts are linked to adolescent psychological problems universally and cross-culturally is a question that needs more empirical investigation. The current study used a sample of 1087 adolescents (M = 13.19 years, SD = 0.90, 50% girls) from 12 cultural groups in nine countries including China, Colombia, Italy, Jordan, Kenya, Philippines, Sweden, Thailand, and the United States to test the cultural moderation of links between parent solicitation, parent behavior control, adolescent disclosure, and adolescent secrecy with adolescent internalizing and externalizing problems. The results indicate that adolescent-driven communication, and secrecy in particular, is intertwined with adolescents’ externalizing problems across all cultures, and intertwined with internalizing problems in specific cultural contexts. Moreover, parent-driven communication efforts were predicted by adolescent disclosure in all cultures. Overall, the findings suggest that adolescent-driven communication efforts, and adolescent secrecy in particular, are important predictors of adolescent psychological problems as well as facilitators of parent–adolescent communication.